A different language: implementing the total communication approach - Charlotte Wilson (Scottish Journal of Residential Child Care)
The majority of people with a learning disability have a communication impairment; however, difficulties with communication are not limited to children with disabilities. In spite of this the importance of communication is often overlooked. This article explores the implementation of the total communication approach in a residential short breaks unit, as a way towards improving communication. In doing so it aims to provide a clearer understanding of the total communication approach, as a model that values all modes of communication. Through this, the impact of communication on efficacy, participation, meaning making, behaviour, containment, attachment, and relationships will be considered.